Comparison of Outcome between Limberg Flap and Karydakis Flap in Pilonidal Sinus Disease: Limberg versus Karydakis Flap in Pilonidal Sinus - Shahid, Madeeha; Khalid, Muhammad; Qamar, Nazia; Zafar, Salman; Sundus, Sadia; Rehman, Abdul (Pakistan Journal of Health Sciences, 2024)
There was controversy regarding the treatment options for pilonidal sinus disease (PSD). Even though a number of techniques were used, such as Karydakis flap, Limberg flap, Bascom cleft lip treatment, and marsupialization, the most effective technique was still up for debate with lower rate of wound infection and recurrence of disease. Objective: To compare the outcome between the Karydakis flap (KF) and the Limberg flap (LF) for the treatment of PSD in terms of infection, wound dehiscence, and recurrence. Methods: This quasi-experimental study was conducted after the approval of the Ethical Committee Board of the Surgery Department, PAF Hospital Mushaf, and Fazaia Ruth Pfau Medical College from May 2021 to February 2022. A total 54 patients with PSD were selected and divided into two groups. The KF and the LF procedure was performed. Outcomes assessed included wound infection, wound dehiscence, and recurrence over a 1-year follow-up. Results: All patients were male in both groups. Wound infection occurred in 6 patients (22.2%) in group KF compared to 1 patient (3.7%) in group LF (p = 0.049). Wound dehiscence was noted in 4 patients (14.8%) in group KF but was absent in group LF (p = 0.039). Recurrence occurred in 3 patients (11.1%) in group KF, while no recurrence was observed in group LF during the follow-up period (p = 0.046). Overall, group LF proved statistically significant superior outcomes compared to group KF. Conclusions: Despite requiring demanding surgical skills, the Limberg Flap proved to be a preferred and reliable technique in the treatment of primary and recurrent sacrococcygeal PSD. It revealed lower rates of wound infection, dehiscence, and recurrence, making it an effective surgical treatment for natal cleft PSD.